Medication-related osteonecrosis of the jaw – case report and current therapeutic recommendations - Sadoń, Aneta; Kukwa, Andrzej; Sulik, Marian (Journal of Stomatology, 2017)
Introduction. Medication-related osteonecrosis of the jaw – MRONJ is a disease characterised by presence of denudated bone in facial skeleton inside oral cavity or though fistulas, persisting for over 8 weeks, during or following concomitant either antiresorptive or antiangiogenic therapy, without previous radiotherapy in head and neck region in anamnesis according to American Associaton of Oral and Maxillofacial Surgeons (AAOMS).1 MRONJ is connected with several groups of drugs: bone metabolism modifying agents (bisphosphonates – BPs denosumab), antiangiogenic (sunitynib, bevacizumab) and used in organ transplantation and oncology (sirolimus, everolimus). Condition described usually affects patients treated due to disseminated solid cancers with skeletal involvement, when above mentioned drugs are applied to prevent skeletal-related events (SREs). Case report. Patient described in this paper had been treated with sunitynib at the beginning of chemotherapy because of disseminated renal-cell carcinoma with metastases to lungs and bones, followed with everolimus thereafter. The event prior to MRONJ occurrence had been teeth extractions in lateral aspect of the mandible on the right side. There was antibiotics therapy, conservative as well as surgical treatment applied in treatment. Finally, fistula closure was obtained. Discussion. Exact, complex etiopathogenesis of MRONJ still remains unclear. Mechanisms of action in each groups of drugs (inhibiting potential of new blond vessels growth and wound healing), specifity of facial bones and existence of MRONJ „triggering event” in most cases are underlined by many authors.1-6,8,10,13 Conservative treatment based on symptomatic action and systemic prevention of infection and surgical debridement in advanced cases are used in therapy. The role of prophylaxis before introducing chemotherapy and special procedure protocol in cases when tooth extrations are necessary are underlined.8 Conclusion. MRONJ is a rare disease, worsening greatly patients’ comfort of life, which etiology is still not exactly explained, demanding further study and adequate animal model.